Nutrition in Cordoba at the End of the 18th Century. An Interpretation from the Perspective of Everyday Spaces and Objects - Moreyra, Cecilia (Revista Complutense de Historia de América, 2012)
Nutrition is a social practice that involves not only a determined food and the body that consumes it, but also spaces and objects. This article attempts to approach nutrition from a socio-cultural perspective, as an aspect of everyday life in Cordoba (Argentina) at the end of the 18th century, employing as a gateway the different spaces of the home in which food was prepared, and the diverse objects utilized for the purpose. The point of departure is a broad notion of material culture, by which objects not only produce physical effects, but also communicate and express social meanings that are shaped by the permanent interrelation between subject, object and space.